Evaluation of elite cardamom (Elettaria cardamomum) genotypes for yield, quality and resistance to Cardamom mosaic virus - Sharon Aravind*, N.K. Leela, R. Senthil Kumar, D. Prasath,; C.N. Biju; M. Anandaraj, M.N. Venugopal, S.J. Ankegowda, (Journal of Plantation Crops, 2017)
Nine genotypes of cardamom (Elettaria cardamomum Maton) along with two commercial cultivars, Green Gold and Appangala 1 were evaluated for their yield and selected horticultural traits. There were significant differences amongst different genotypes with respect to yield and other traits. The genotype IC 349651 was found to be highest in yield (1048.2 kg ha-1) followed by IC 547167 (987.1 kg ha-1). The genotype IC 547167 (Appangala 2) was found to be moderately resistant to Cardamom mosaic virus under artificial conditions and rich in Î± terpinyl acetate content which was comparable to Appangala 1. In 2014, the genotype IC 547167 was recommended for high yield and resistance to Cardamom mosaic virus under field conditions and released as Appangala 2 for Karnataka and adjoining areas of Kerala. The variety, Appangala 2 (IC 547167) was developed through hybridization between Appangala 1 x NKE 19.